Peran Orang Tua dalam Mengembangkan Kecerdasan Emosional Anak - Meriyati, Meriyati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2014)
One effort that can be done is to prepare the cognitive intelligence and emotional intelligence. Emotional intelligence is more aimed at the effort to recognize, understand and manifest emotions in the right portion and the effort to manage emotions in order to be controlled so that can be utilized to solve various problems faced later. Through IQ people can face the real world, but the individual needs emotions in order to understand and confront himself and ultimately be able to face others, so important we build emotional intelligence of children for future preparation. By having an emotional intelligence someone will better understand and appreciate feelings on self and others and can apply it effectively in everyday life.